Study the Problems of Caring for the Elderly in Muslim Families in the Bannangsta Subdistrict, Bannangsta District, Yala Province - Machae, Rohanee; Jarong, Afnan; Khareng, Mutsalim (MENARA : Journal of Islamic and Contemporary Issues, 2022)
This research aims 1) to study the care of the elderly according to Islamic provisions 2) to study of problem in the care for the elderly in Muslim families in Bannangsta subdistrict, Bannangsta district, Yala province. Through learning Al-Quran statue, Al-Hadith, books, associated academic papers and data were collected from a sample of 19 elderly caregivers in Bannangsata subdistrict. The samples were selected by simple random sampling method, and its number based on Krejcie and Morgan table. The tool used was a questionnaire with Cronbach's alpha coefficient of reliability 0.76 and 0.80 and with IOC > 0.5. Data were analyzed by using mean and standard deviation. The data were collected from 4 interviewees, then analyzed, summarized and presented descriptive data. The research results were found that 1) Islam has clearly indicated the importance of caring for the elderly, such as gratitude, practice, care and care for the elderly by stipulating that Muslims should have a basis for caring for and adhere to the principles of caring for the elderly according to Islamic provisions. To make Muslims realize the care of the elderly 2) Problems in caring for the elderly in Muslim families found that most of the sample group used religious, it was found that most of the sample group used religious doctrine as a guideline for caring by allowing the elderly to always remember Allah, always paying attention to the elderly and taking care of the elderly in terms of living, environment, eating and treatment at a moderate level. It was representing the mean 3.21 and standard deviation of 1.06. According to the analysis of the survey of caregivers, there are guidelines or methods for caring for the elderly according to Islamic principles. children should always give importance and support to the elderly, Did not make the elderly feel alone and discouraged for the rest of their life.